Method for extracting the surface impedance of a generic reflective metasurface - J. G. Smith; I. R. Hooper; N. Clow; A. P. Hibbins; S. A. R. Horsley (Scientific Reports)
Abstract We develop a method for the extraction of the surface impedance tensor of a generic reflective metasurface using an analytic relation between the tensorial surface impedance and the four polarisation-dependent reflection coefficients. We apply this technique to experimental data obtained from a metasurface with a rhomboidal unit cell in the 16–26 GHz range, but note that it could be applied to reflective metasurfaces in any frequency regime. The extraction method can also be applied to model data to facilitate the design process of spatially graded tensorial metasurfaces that allow for full control of the form of the scattered field.